Complex delivery project performance improvement by standardized schedule development and scheduling system establishment - Hällilä, Johanna (My University, 2019)
Multinational companies involved in project businesses often struggle with the delivery of large complex projects. Strong competition among those companies demands shorter delivery times and higher project performances. Meanwhile, the complexity and uncertainty of the projects has increased, which has a negative impact on the project delivery times which consequently increases the risk of contractual penalty fees. In such complex business environments, organizations need to understand project complexity better and find tools and processes to manage it. The project organization that assigned the work had a need to improve complex projects deliveries. The objectives of this study were to find and collect interdependencies between the project activities, estimate the activity durations and develop a standardized project template for the delivery project lifecycle. Finally, a scheduling system on Oracle Primavera P6 project management software was developed, which in the end of the study was implemented in the organization’s daily use. The research was conducted as a multi method case study. In order to obtain a solution for the target business’s needs, the data collection was performed by semi-structured interviews, quantitative historical data and organizational collaboration. In the beginning of the study, the organizational environment was analyzed in the context of complex projects in order to outline the project environment. Then the schedule’s activity interdependencies were collected and after that, analyzed with tools intended for analyzing complex information flows and processes. From these results, a project bottleneck analysis was carried out. After the data collection and analysis, the standard template for the projects was developed and finally the schedule system and suggested processes were introduced by practical user training sessions. As a result, the organization has now a standardized framework with improved project performance capabilities for concurrent projects. In addition, a number of processes for the project scheduling and controlling were proposed and the personnel has now a good knowledge of the new environment, as a result of this research study. For the future, this provides a robust basis for continuous improvement in projects performances.
Keywords: Complex project, performance improvement, scheduling system, Oracle Primavera P6; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management